A short history of nearly everything - Bryson, Bill (New York Broadway Books, 2003)
Bryson explores scientific discoveries, the history of science, and how humanity has come to understand the universe$1 (Bfrom the Big Bang to modern physics and biology$1 (Bpresented in an engaging and accessible narrative.s
Includes bibliographical references and index.
Keywords: Science -- Popular works; Universe -- History; Scientific expeditions -- History; Scientists -- Biography